4Å1λ£₁λ¨Â¦¦s¦¦*O+
Pas plus court que la réponse 05AB1E existante , mais je voulais essayer la fonctionnalité récursive de la nouvelle version 05AB1E comme pratique pour moi-même. Pourrait peut-être être joué par quelques octets. EDIT: Et il peut en effet, voir la version récursive de @Grimy réponse 05AB1E s » ci - dessous, qui est de 13 octets .
Sort le premier narticles: Essayez-le en ligne .
Pourrait être changé en base 0 n'e élément lors du remplacement £
par è
: Essayez-le en ligne ;
ou une liste infinie en supprimant £
: Essayez-le en ligne .
Explication:
Cela implémente la formule utilisée dans la description du défi comme ceci:
a ( n ) = a ( n - 1 ) + ∑n - 1k = 2( a ( k ) ⋅ a ( n - 1 - k ) )
a ( 0 ) = a ( 1 ) = a ( 2 ) = a ( 3 ) = 1
λ # Create a recursive environment,
£ # to output the first (implicit) input amount of results after we're done
4Å1 # Start this recursive list with [1,1,1,1], thus a(0)=a(1)=a(2)=a(3)=1
# Within the recursive environment, do the following:
λ # Push the list of values in the range [a(0),a(n)]
¨ # Remove the last one to make the range [a(0),a(n-1)]
 # Bifurcate this list (short for Duplicate & Reverse copy)
¦¦ # Remove the first two items of the reversed list,
# so we'll have a list with the values in the range [a(n-3),a(0)]
s # Swap to get the [a(0),a(n-1)] list again
¦¦ # Remove the first two items of this list as well,
# so we'll have a list with the values in the range [a(2),a(n-1)]
* # Multiply the values at the same indices in both lists,
# so we'll have a list with the values [a(n-3)*a(2),...,a(0)*a(n-1)]
O # Take the sum of this list
₁ + # And add it to the a(n-1)'th value
# (afterwards the resulting list is output implicitly)
Version 13 octets de @Grimy (assurez-vous de voter pour sa réponse si vous ne l'avez pas encore fait):
1λ£λ1šÂ¨¨¨øPO
Sort le premier n items: Try it online.
Can again be changed to 0-based indexing or an infinite list instead:
- (0-based) indexing 1λèλ1šÂ¨¨¨øPO
: Try it online;
- Infinite list λλ1šÂ¨¨¨øPO
: Try it online. (Note that 2 bytes are saved here instead of 1, because the recursive environment starts with a(0)=1 by default.)
Explanation:
This instead implements the formula found by @xnor for his Python answer like this:
a(n)=∑n−1k=2(a(k)⋅a(n−2−k))
a(−1)=a(0)=a(1)=a(2)=1
λ # Create a recursive environment,
£ # to output the first (implicit) input amount of results after we're done
1 # Start this recursive list with 1, thus a(0)=1
# Within the recursive environment, do the following:
λ # Push the list of values in the range [a(0),a(n)]
1š # Prepend 1 in front of this list
 # Bifurcate the list (short for Duplicate & Reverse copy)
¨¨¨ # Remove (up to) the last three value in this reversed list
ø # Create pairs with the list we bifurcated earlier
# (which will automatically remove any trailing items of the longer list)
P # Get the product of each pair (which will result in 1 for an empty list)
O # And sum the entire list
# (afterwards the resulting list is output implicitly)
a(n-1-k)
àa(n-k)
, n'est -ce pas?